The Kewangkey Tradition of Borneo (Dayak) and the Catholic Church's Teachings on Life After Death: A Comparison and Reflection on Faith - Tiyo, Tiyo; Nampar, Hilario Didakus Nenga (PT Literasi Nusantara Publisher, 2022)
This study uses a qualitative approach. The data sources for this research are traditional leaders who understand the Kewangkey ceremony. Data collection techniques were carried out through interviews, observation, and documentation. The results of this study indicate similarities in the objectives of praying for the spirits and differences in time. The values ​​of life after death can be seen through several elements in the Kewangkey ceremony, namely the religious aspect: bodily resurrection, purification, judgment, and heaven; and social factors: gathering together, helping each other, and brotherhood. The study has limitations as it covers only a small number of respondents in one locus. Future research is suggested to investigate a wide range of respondents. This research contributes to the pastoral work of the Catholic Church that the understanding of life after death is expected to be lived by Catholics who come from the Benuaq Dayak Tribe. So that it is increasingly believed that God himself created man so that He alone will take care of man and free man from sin. Therefore, the results of this study are appropriate to be used as catechesis for the Catholic Benuaq Dayak community.